Bataille's "The Solar Anus" or the Parody of Parodies - Leslie Anne Boldt-Irons (Studies in 20th & 21st Century Literature, 2001)
Bataille uses parody in "The Solar Anus" to attack the concepts underpinning Cartesian, Hegelian, Romantic and Surrealist discourses. Each one of these discourses lays claim to an impossible achievement: that of arriving at a "total identification," whereby the subject attempts to embrace a "transcendent whole." Bataille uses his parodic cosmogony in "The Solar Anus" to subvert these discourses, showing them to be incapable of exhausting the subject of their study. On another level as well, Bataille's "Solar Anus" challenges any attempt at parody. Within the context of his global parody, each target of parody is itself parodic of another target, without possible end. In this manner, Bataille refuses to allow the establishment of a new discourse or value that would be transcendent vis-a-vis the target of his parody.
Keywords: Bataille; The Solar Anus; parody; Cartesian; Hegelian; Romantic; Surrealist; discourse; total identification; transcendent whole; parodic cosmogony; global parody